Simultaneous robotic surgery with low anterior resection and prostatectomy/hysterectomy - Itatani, Yoshiro (Int Cancer Conf J, 2019)
Cooperation with multiple departments is essential for the treatment of patients with rectal cancer and other pelvic cancers. In our department, we experienced two cases of rectal cancer that underwent robotic low anterior resection (LAR) and simultaneous resection of other pelvic organs (case 1 with prostatectomy and case 2 with hysterectomy) using the da Vinci Xi system. Here, we show the precise procedures of these two robotic surgeries. Under general anesthesia and lithotomy position, five da Vinci ports were symmetrically placed along the umbilical horizontal line with a 7 cm interval, and a 5 mm AirSeal Access Port was added in the right or left upper quadrant. Patients were placed with 22-degree Trendelenburg and 8-degree tilt to the right. The operators used the center port on the umbilicus as a camera port and chose the docking arms with either two-left-one-right or one-left-two-right setting depending on their preference. This port setting was quite useful for the operators from multiple departments to change the docking arms, even if their preference may be different. Moreover, assistants could use the remaining two ports to provide a well-expanded and safer surgical field. “With a familiar view” and “with a wide view” are our two concepts to safely perform extended pelvic surgeries. We have employed this symmetrical horizontal port site position as a general setting for usual rectal surgeries. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13691-019-00377-3) contains supplementary material, which is available to authorized users.